The Role of InceptionV3 as Real-time Facemask Detection in the Health, Social, and Economic Fields During the COVID-19 Pandemic - Amal Khairan; Muhammad Fhadli (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The corona virus disease 2019 (COVID-19) pandemic has made all activities in human life run at a slower tempo, whereas humans are used to super-fast changes. In the health sector, the pandemic places a huge burden on the health system, including hospitals. While, economically, supply chain and production are disrupted, and the tourism industry dies. From the social side, the existence of social distancing puts psychological pressure on the community. Finally, various ways are used to support human life during this pandemic, including utilizing artificial intelligence or known as AI. One of the popular AI applications to be developed during this pandemic is facemask detection used in public areas. Therefore, in this study, the author tries to develop a facemask detector that could detect the use of masks in real time. The research aims to analyze the role of inceptionV3 as real-time facemask detection in the health, social, and economic fields. As a result, the author got 97% accuracy which is much higher than using vanilla convolutional neural network or known as CNN. The existence of the COVID-19 pandemic has had a tremendous impact on almost all people in the world, not least in Indonesia where the Ministry of Health and the relevant Government have issued health protocols to minimize exposure caused by the COVID-19 pandemic. There needs to be an inspection of masks, where the role of inceptionV3 as real-time facemask detection is to help monitor social activities such as weddings, celebrations, entertainment, and so on. Implement inceptionV3 as real-time facemask detection which helps the economic process, for example in traditional markets, which are free to transact if they wear masks, and strict action will be taken against those who do not wear masks